Facile synthesis and characterizations of mof-5 coordination polymer with various metal linker ratios for ammonia gas storage - Misran H.; Aminuddin A.M.; Zini F.A.M.; Ghazali M.J.; Ramesh S. (2023)
Metal-organic framework coordination polymer materials of MOF-5 with Fm3m cubic structure and tetrahedral structure were successfully synthesized at room temperature and pressure using liquid-crystal (i.e. surfactant) templating method and direct mixing method. The crystallinity increased as metal (Zn)/linker (benzenedicarboxylic acid, BDC) ratios were varied from 0.3 to 0.5. However, the cubic structure of evacuated framework was relatively disrupted at metal/linker ratio of 0.7. Direct-mixing synthesis approach resulted in MOF-5 with layered tetragonal structure due to the increased mobility of the organic-linker as the metal/linker ratios were increased. On the other hand, liquid-crystal templating method resulted in MOF-5 with cubic structure with sizes of ca. 3-5 micron. Changing the solvent from dimethylformamide to chloroform during the synthesis affected the size of the single cubic to decrease from 5 micron to 3 micron, respectively. Furthermore, MOF-5 prepared with metal/linker ratio 0.5 and aged in solvents with higher crystallinity exhibited higher ammonia adsorption uptake at ca. 7.2%. 2010 American Institute of Physics.